Quantification of AMY1 gene copy number and its association with glycemic response. - Lee, Jin Shun. (2013)
There has been no study to date which measures salivary amylase AMY1 gene copy number variation (CNV) in an Asian population, with varying prevalence of obesity and Type 2 Diabetes Mellitus (T2DM). The aim of this study is to investigate how the differences in CNV of AMY1 between individuals can influence postprandial glycemic response (GR), which is a well recognized and established risk factor that precipitates the development of T2DM. Healthy, non-obese, young men were recruited and asked to consume glucose solution (GS) (50g of anhydrous glucose dissolved in 250ml of water) as reference food and 50g of available carbohydrate from basmati (BR) or jasmine rice (JR) as test food, after fasted for 10 to 12 hour overnight. Buccal swabs and capillary bloods were taken for the measurement of AMY1 gene copy numbers and postprandial GR respectively. From the small number (n=9) of subjects that we analyzed, we found no significant correlation between subjects' AMY1 gene copy number and postprandial mean incremental Area under Curve (iAUC) values. Further analysis with a larger number of subjects is warranted for a statistically significant conclusion to be made. We recommend comparison between different ethnic groups to be made when sufficient subjects are recruited.